2011
DOI: 10.1177/1934578x1100600618
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Argentinean Propolis Collected in Extreme Regions and its Relation with Antimicrobial and Antioxidant Activities

Abstract: This paper reveals, for the first time, the functional properties of propolis from an extreme region of Argentine (El Rincón, Province of Catamarca, Argentina), as well as the isolation and identification of bioactive compounds. The antioxidant activity was determined by the ABTS method and β-carotene bleaching. The antibacterial activity was determined on methicillin resistant Staphylococcus aureus (MRSA) by the microdilution method and bioautographic assays. Twelve compounds were isolated and identified by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 8 publications
3
20
0
Order By: Relevance
“…EPA and EPB inhibited significantly (100%) the clinical strains of MRSA and of S. aureus ATCC 6538 and ATCC 25923. Our results were similar to others reports in relation to the MRSA (Vera et al 2011, Astani et al 2013, Aguiar et al 2014) and S. aureus ATCC 6538 (Hazem et al 2017). In opposition, AL-Ani et al (2018) observed a moderate anti-MRSA efficacy and Katircioglu & Mercan (2006) a low efficacy against S. aureus ATCC 25923, reinforcing the importance of the evaluation of multiresistant strains in the tests of antimicrobial activity of natural products (Cos et al 2006).…”
Section: Discussionsupporting
confidence: 93%
“…EPA and EPB inhibited significantly (100%) the clinical strains of MRSA and of S. aureus ATCC 6538 and ATCC 25923. Our results were similar to others reports in relation to the MRSA (Vera et al 2011, Astani et al 2013, Aguiar et al 2014) and S. aureus ATCC 6538 (Hazem et al 2017). In opposition, AL-Ani et al (2018) observed a moderate anti-MRSA efficacy and Katircioglu & Mercan (2006) a low efficacy against S. aureus ATCC 25923, reinforcing the importance of the evaluation of multiresistant strains in the tests of antimicrobial activity of natural products (Cos et al 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The results indicate that these structures are the most favourable for antibacterial activity within the flavonoid family (Zampini et al, 2005;Agüero et al, 2010;Vera et al, 2011). The same effect was obtained with other chalcones and flavanones previously investigated (Olivella et al, 2001;Nowakowska, 2007;Agüero et al, 2010;Vera et al, 2011). In this work, the anti-streptococcal in vitro activities of Zuccagnia punctata crude extract and HF were also observed in vivo when their activities were evaluated in a Streptococcus pneumoniae infection model in mice.…”
Section: Discussionsupporting
confidence: 80%
“…The highest in vitro activity of isolated compounds was observed for assayed chalcone and flavanone (DHC and HF, respectively). The results indicate that these structures are the most favourable for antibacterial activity within the flavonoid family (Zampini et al, 2005;Agüero et al, 2010;Vera et al, 2011). The same effect was obtained with other chalcones and flavanones previously investigated (Olivella et al, 2001;Nowakowska, 2007;Agüero et al, 2010;Vera et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…It has been used in folk medicine from ancient times for its pharmaceutical properties and has been extensively studied in many countries [4,5]. It is reported to possess various biological activities, such as antibacterial [6,7], antiviral [6,8], antifungal [6,9], antiinflammatory [10], antihepatotoxic [11], anticancer [12,13], antitumor [14,15], and antimutagenic [16] properties. For these reasons, it is extensively used in foods, beverages, and dietary supplements to improve health and to prevent diseases [5,17].…”
mentioning
confidence: 99%